Independent and interactive associations of dietary nitrate and salt intake with blood pressure and cognitive function: a cross-sectional analysis in the InCHIANTI study. (19th May 2022) - McGrattan, Andrea M.; Stephan, Blossom C. M.; Shannon, Oliver M.; Mazidi, Mohsen; Gilchrist, Mark; Smallwood, Miranda; Winyard, Paul; McMahon, Nicholas; Blekkenhorst, Lauren C.; Mohan, Devi; Bandinelli, Stefania; Robinson, Louise; et al.
Abstract: Blood pressure (BP) control is a key target for interventions to reduce cognitive decline. This cross-sectional study explored associations between objective (24-hour urine excretion) and subjective (food frequency questionnaire [FFQ]) measures of dietary sodium and nitrate intakes with cognitive function and resting BP in the InCHIANTI cohort. Baseline data from 989 participants aged >50 years were included. In fully adjusted models, participants with concurrent high nitrate and low sodium (Odds Ratio (OR)=0.49, 95%CI 0.32–0.76, p = 0.001) and high nitrate and high sodium (OR = 0.49, 95%CI 0.32–0.77, p = 0.002) 24-hour urinary concentrations had lower odds of high BP than participants with low nitrate and high sodium concentrations. We found no significant associations between sodium and nitrate intakes (24-hour urinary concentrations and FFQ) and poor cognitive performance. Urinary nitrate excretion was associated with lower BP and results appeared to be independent of sodium intake. Further analyses in longitudinal studies are required to substantiate these findings.